All the presidents' bankers : the hidden alliances that drive American power - Prins, Nomi (Nation Books, 2014)
"All The Presidents' Bankers is a compelling narrative of how a small group of private bankers and their financial institutions shaped America's economy and its global position since the start of the twentieth century. Through personal, political and professional networks, these bankers strategically exercised, and continue to exercise, disproportionate control over the destiny of billions of people. Nomi Prins offers an explosive account of how this came to be, and how the banks continue to influence the world economy and dominate government. Aligning the complex relationships between political and financial leaders since the early 1900s, Prins exposes the elite bankers that served as unelected leaders and confidants, acting as a shadow government concealed behind the US presidency from Wilson to Obama. With eye-opening correspondence culled from Presidential libraries across the country, against a timeline of two world wars and multiple market crashes, All The Presidents' Bankers traces the shocking consequences of a system in which there is no line between public office and private power"--